An An Exploration of High School Students’ Errors in Solving Trigonometry Problems - Alfitri, Putri Armania Agustina; Kurniati, Nurdiyah; Prabawanto, Sufyani; Yulianti, Kartika (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
Trigonometry plays an important role in the field of mathematics education, but in fact, some errors are identified. Therefore, this study aims to explore the students’ errors in solving trigonometry problems, especially in the sub-topics of trigonometric ratios. This is a qualitative study using a case study design. The subjects of this study were 35 students in grade 10 in one of the senior high schools in a district located in the Province of East Kalimantan. The research instruments were 1) a diagnostic test consisting of five essay problems about trigonometric ratios; 2) observation sheets; and 3) interview guidelines. The data was analyzed through three processes. They were: 1) data reduction, 2) data presentation, and 3) conclusion drawing or verification. The results show that the subjects made errors in solving trigonometric ratio problems, with the most errors made by subjects being errors in understanding concepts and writing algorithms. The causes of students making errors are due to the weak understanding of students' concepts, lack of student mastery of the prerequisite topics, the problems given being less varied, and students being in a hurry to solve problems.